Seasonal ice-covered lake surface likely caused the spatial heterogeneity of aeolian sediment grain-size in the source region of Yellow River, northeastern Tibetan Plateau, China - Hu, Guangyin; Hu, Jingjing; Dong, Zhibao; Yang, Linhai (Frontiers in Earth Science, 2023)
The area of lakes in Tibetan Plateau (TP) is 36522 km2, accounting for nearly half (49.1%) of the total lake surface area in China, and the lakes in TP are seasonally ice-covered for 4–5 months per year. In such a high-cold Third Pole with extensive lakes, how does aeolian sediment transport on ice cover and to what extent can seasonal ice-covered lake cause sediment redistribution by providing pathways for sediment migration is rarely studied. The source region of Yellow River (SRYR) is located in the northeastern TP with an altitude above 4000 m, is home to large area of seasonal frozen lakes. Nine sections of aeolian sediments were collected from SRYR for grain-size study. The end-member modeling analysis (EMMA) provides a greater chance of resolving aeolian sediment sources since it can quantitatively separate the particle size components of various sedimentary dynamic processes and sources in the sediment. The result shows great spatial difference of the mean grain sizes (mainly varying between 70 and 230 μm). Parametric EMMA is applied to study the provenance tracing of aeolian sediment, combining with remote sensing images and wind data. Aeolian processes were analyzed by separating and extracting the grain size end-members of nine sections, and four statistical end-members (modal grain size is 8.9, 79.5, 141.6, and 251.8 μm, respectively) were classified from the grain size distribution. It shows that the sedimentary sequences in sections 7 and 8 have high EM2 and EM3 fractions and very low EM4 content at all depths. Based on comprehensive analysis of aeolian sediment grain-size, phenology of ice lake, wind regime and remote sensing images, it revealed that the fine aeolian sediments (sections 7 and 8) on the downwind shore of Ngoring Lake likely transported from the upwind shore, which were blown across the ice-covered lake surface by prevailing west wind in winter and spring, but the coarse sediments could be trapped by ice cracks. Therefore, it’s concluded that the aeolian sediment transport on seasonal ice-covered lakes may lead to the spatial heterogeneity of aeolian sediment grain-size in the SRYR.